2017
DOI: 10.1016/j.paid.2016.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Reacting to unexpected losses in an uncertain world: High approach individuals become even more risk-seeking

Abstract: Previous research has shown that people are risk-seeking in the face of losses. We propose that this risk-seeking orientation is a palliative approach response to deal with a discrepancy between people's desires of having no losses versus the possibility of loss. An expectancy violation (which induces behavioral approach responses) would therefore strengthen people's risk-seeking in the context of losses. Two experiments (Study 1 and Study 2) which were conducted in the context of the Asian Disease Problem dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The result is contradictory to statements that claim that individuals are more sensitive to losses than to gains. [72][73][74][75] However, it is consistent with the findings of a prior study, which concluded that communicating the benefits of mitigation efforts, rather than the potential negative consequences of not taking actions, can result in more positive responses from citizens. 71 Similarly, positive outcome framing can strengthen…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The result is contradictory to statements that claim that individuals are more sensitive to losses than to gains. [72][73][74][75] However, it is consistent with the findings of a prior study, which concluded that communicating the benefits of mitigation efforts, rather than the potential negative consequences of not taking actions, can result in more positive responses from citizens. 71 Similarly, positive outcome framing can strengthen…”
Section: Discussionsupporting
confidence: 87%
“…71 In contrast, investigations also find that individuals are more sensitive to losses than to gains and highly evaluate risks when making decisions. [72][73][74][75] However, loss framing, as a moderator, is more effective in influencing individuals' waste recycling behaviors when paired with concrete mindsets, whereas gain framing is more efficacious when paired with abstract mindsets. 68 Compared with concrete personal gains or losses, the environmental pollution issue involves relatively abstract and public interests.…”
Section: Moderating Role Of Outcome Framingmentioning
confidence: 99%